3D printing of complex-shaped polymer-derived ceramics with enhanced structural retention. Issue 11 (18th August 2022) - Liu, Jian; Xiong, Shufeng; Mei, Hui; Chen, Zhangwei
ABSTRACT: The combination of polymer-derived ceramics and DLP 3D printing has significant advantages for manufacturing special polynary ceramics with complex structures. However, a large number of the organic components in the precursor rapidly burn out and release after evaporation during pyrolysis. This leads to structural retention issues such as sample deformation, shrinkage and cracking. The surface morphology and accuracy of the sample are greatly affected by the escape of organic matter and the release of thermal stress during the pyrolysis process. Therefore, this study employs the method of adding low-melting-point silicone oil based on the original material components. The slow burn-out process of silicone oil at a lower temperature can produce fine pores, which would aid the release of thermal stress. Additionally, it can provide channels for escape of the organic gas at high-temperature, which helps to reduce large deformation and cracking and improves the surface morphology and dimensional accuracy of the final pyrolyzed samples. The method studied in this work helps to enhance the structural retention of complex-shaped polymer-derived ceramics manufactured by 3D printing and high-temperature pyrolysis, which could be beneficial to the further mass fabrication of such ceramic products.